РАЗЛИЧНЫЕ УРОВНИ ТВОРЧЕСКОГО САМОРАЗВИТИЯ СТУДЕНТОВ - Кадырова, М.Р. (SCIENCE and SOCIETY, 2016)
The article is devoted to the development of creative qualities of a human personal, creative personality problems at all levels of education and training. The complex effects required for the formation of a creative personality creative abilities of the individual components of the student are focused on the creative qualities of the person.
Keywords: creative; value; personal; creative personality; formation